Efektivitas Edukasi Bahaya Pergaulan Bebas dan HIV/AIDS pada Siswa MTSN 1 Konawe Selatan - Hartati Bahar; Shabilla Ananta Putri Baso; Gita Marzan Cahyani; Wa Ode Fazrah Fatimah; Putri Kalsum; Tatya Devina Pratiwi6; Tabita Sombo (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Adolescents are classified as an age group vulnerable to various health and social issues, including engagement in promiscuous behavior, which is considered to carry a high risk of HIV/AIDS transmission. According to national data from 2022, Southeast Sulawesi was ranked 29th with a total of 1,516 reported cases of HIV/AIDS. In Kendari City, 272 new cases were recorded from January to November 2022. Meanwhile, in South Konawe Regency the site of this study 9 HIV cases were reported in 2023 and 5 cases in 2024. This study was conducted with the aim of improving students’ knowledge regarding the dangers of promiscuity and HIV/AIDS through the implementation of educational activities carried out at MTSN 1 South Konawe. The method employed in this study was a quantitative approach using a pre-experimental design, specifically a one-group pretest-posttest design. The population of this study consisted of 30 students from grades VII and VIII at MTSN 1 South Konawe in the year 2025. The sampling technique used was purposive sampling, with a total of 30 respondents selected. Data were collected using questionnaires administered to respondents before and after an educational session was delivered using the interactive educational game